STRATEGI SSCS (SEA SHEPHERD CONSERVATION SOCIETY) DALAM MENGATASI PERBURUAN PAUS OLEH JEPANG - Fitrah Annisa; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Sea Shepherd Conservation Society is an environmental organization whose mission is to protect defenseless marine wildlife and end the destruction of habitats in the world's oceans. SSCS, which carries out many operations to save marine habitats, especially mammals, saw how Japan's actions in conducting whale hunting for the purpose of this research were actions that were dangerous to marine ecosystems and endangered whales as living things whose existence is protected. The purpose of this research is to explain the SSCS strategy in overcoming Japanese whaling. This study used the Constructivist theory by Alexander Wendt who believe that social structure is determined more by shared ideas rather than material drives and actors' identities and interests. This study used a qualitative research method by collecting data through a Documentation Study, namely collecting data by viewing and analyzing documents made by the subject himself or by other people on the subject in the form of journals, books and other documentation in the form of videos from the subject himself or social media. SSCS succeeded in stopping whaling by the Japanese for research purposes through their direct action in JARPA II research. By leveraging the media, SSCS also succeeded in attracting attention from the world community regarding Japanese whaling activities through their television series which managed to survive until its sixth season. Keywords: SSCS, NGO, Cetacea